2021
DOI: 10.1002/lary.29494
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dental Care in Head and Neck Cancer Outcomes: A Systematic Review and Meta‐Analysis

Abstract: Objective/Hypothesis The objective of this study was to perform a systematic review and meta‐analysis to determine the impact of dental care on head and neck (H&N) cancer survival. Methods A comprehensive literature search was performed using PubMed, MEDLINE, and CINAHL to find all relevant studies from the date of inception to March 2020. Systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, and meta‐analysis was performed using the random eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Thus, it is premised that prosthetic status and needs of head and neck cancer irradiated subjects may differ from those of individuals not under radiotherapy as well as healthy individuals. [12][13][14] The present study showed that there was a statistically significant difference in the proportion of patients using prosthesis among those who had undergone radiotherapy and those who were not given radiotherapy. The proportion of people using prosthesis was lower in the irradiated patients as compared to radiated ones.…”
Section: Discussionmentioning
confidence: 49%
“…Thus, it is premised that prosthetic status and needs of head and neck cancer irradiated subjects may differ from those of individuals not under radiotherapy as well as healthy individuals. [12][13][14] The present study showed that there was a statistically significant difference in the proportion of patients using prosthesis among those who had undergone radiotherapy and those who were not given radiotherapy. The proportion of people using prosthesis was lower in the irradiated patients as compared to radiated ones.…”
Section: Discussionmentioning
confidence: 49%
“…Regular dental visits provide frequent opportunities for dentists to detect OC/OPC at earlier stages. (33,34,46,47) Likely as a result, routine dental care is associated with improved survival from oral cancer, (48,49) and a greater likelihood of incident oral cancer is associated with infrequent dental care.0 (50,51) In our sample, OC/OPC prevalence and incidence both increased with age, with the highest rates in the 60-64 age group in both the Medicaid and commercial insurance groups. That finding is consistent with those of Mahal and colleagues, who noted a unimodal peak in incidence between the ages of 60 to 64.…”
Section: Discussionmentioning
confidence: 76%
“…Regular dental visits provide frequent opportunities for dentists to detect OC/OPC at earlier stages. (33, 34, 46, 47) Likely as a result, routine dental care is associated with improved survival from oral cancer, (48, 49) and a greater likelihood of incident oral cancer is associated with infrequent dental care.0 (50, 51)…”
Section: Discussionmentioning
confidence: 99%
“…The prevention, hygiene, and maintenance program must be individualized and flexible in order to achieve a continuous and progressive educational process. Professional and home oral hygiene with a related instruction prior to maxillofacial surgery contributes to the oral health and well-being of the patient, as well as significantly reducing pneumonia and mortality [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%